Influence of dry pea soaking in various sodium salts solutions on the microstructure and sensory quality of fried peas - Rui Costa; Gaspare Di Gregorio; Andreia Alves; João Noronha; Taha Rababah (Applied Food Research)
Peas (Pisum sativum L.) are a highly consumed legume with significant nutritional and health benefits, including high protein, fiber, vitamin, mineral, and phytochemical content. Although both fresh and dry peas are used in food applications, dry peas are preferred for industrial processing and snack production. Pre-treatment methods, such as soaking and blanching, often involve sodium salts, including sodium chloride, sodium bicarbonate, and sodium carbonate, which influence texture, cooking time, nutritional value, and sensory properties. Sodium salts also play a critical role in saltiness perception, which is a key factor in consumer preference. However, concerns over excessive sodium intake have driven interest in alternative salt reduction strategies.This study evaluated the effects of different sodium salts on pea properties, particularly saltiness, by examining how soaking in sodium salt solutions from 0.2 % to 0.8 % sodium concentrations, covering pH from 7 to 13.5, affects texture, color, and sodium uptake after soaking, pre-cooking, and frying. The goal was to gather knowledge to optimize salt usage in fried pea snacks while considering health implications.The results showed that alkaline solutions generally softened peas but failed to preserve their green color during frying. Higher pH levels of hydroxide and carbonate led to greater sodium uptake; however, sodium chloride remained the most effective in achieving the desired salty taste. These findings underscore the potential of using a strategic combination of salts to enhance texture while maintaining optimal saltiness, offering a viable approach for improving product quality and consumer acceptance.